Analysis of the influence of clamp installation position on vibration stress for spatial pipeline - Lv, Shang; Sun, Wei; Du, Dongxu; Ma, Hongwei; Sun, Xuedong; Ma, Shihao (The International journal of pressure vessels and piping, 2024)
In aero-engines, small changes in the clamp position can sometimes significantly alter the vibration stress of the pipeline system, so there is an urgent need to study the influence of clamp position on pipeline vibration stress. Firstly, a dynamic modeling method of spatial pipeline system is proposed based on the finite element method, the modeling method can more accurately simulate the complex boundary constraints caused by multiple clamps and pipe fittings. Then, an improved dynamic substructure method (reduced-order method) is developed by combining the dynamic substructure method with the clamp position parametric model to improve the efficiency of the subsequent clamp position parameters influence analysis. Further, the rationality and efficiency of the reduced-order modeling approach are verified by numerical and experimental studies. Finally, the influence of the clamp position and the key parameters of different components (pipe body, clamps, fittings) on the pipeline vibration stress is investigated. The results show that when the main vibration region of the pipeline system coincides with the installation region of the clamp, the vibration stress can be significantly reduced by installing the clamp in the maximum modal displacement region of the corresponding pipe segment. The related modeling methods and conclusions can provide valuable references for the dynamics design of pipeline system in engineering practice. [Display omitted] •The massless nodes are introduced via coupling elements to accurately simulate constraint conditions.•A parametric finite element modeling method for a spatial pipeline system supported by multiple clamps and fittings.•An improved dynamic substructure reduced-order modeling method for spatial pipeline system.•The influence of clamp positions on the vibration stress for the pipeline system is analyzed.